Aprender a empreender: um pilar na educação de jovens e adultos. - Leal., Antonio Fernando (2009)
This thesis aims to evaluate the importance of the entrepreneurial education activities offered by Sebrae, especially those related to distance education, considering the changes occurred in the world of work. Based on the pillars of knowledge suggested by UNESCO as relevant to education of people up the XXI century learning how to know; learning how to do; learning how to live together and learn how to be this study suggests as additional issue in the education of young people and adults, the pillar of learning to be an entrepreneur. This type of learning aims to develop the search for autonomy by the participants, in order to face effectively the diverse situations of life, specially those related to the maintenance of themselves and their own families. The assessment is made possible by the analysis of documentary records produced and made available by Sebrae and the literature on the national and international practices related to EJA. Throughout the search has been sought evidences of increasing rates of enterprises survival in the period which educational programs have been offered by Sebrae in mode of EAD, concluding, from survey data, that there is a connection between these offerings and the young people and adults learning assimilation of how to undertake businesses.